Analysis of differences in lay-up shoot ability from the right and left sides of men's basketball extracurricular members - Hardopo Putro, Kukuh; Suharjana, Suharjana; Marhaendro, Agus Susworo Dwi; Arga, Muhammad Wahyu; Srianto, Widha; Widodo, Hary; Amajida, Abiyyu; Ndayisenga, Japhet (Jorpres (Jurnal Olahraga Prestasi), 2023)
The problem in this research is that students are not yet perfect at doing lay-up shoots in both position and movement. This research aims to determine the difference in ability between lay-up shoots from the right side and the left side among boys' basketball extracurricular members aged 11-14 years. This research is a descriptive study using a survey method. The sample in this study was taken by random sampling, totaling 30 students. The instrument of this research is the lay-up shoot test modified. Data collection techniques using test and measurement methods. Data analysis using prerequisite tests and t-tests. The statistical test results showed that the lay-up shoot t-test value on the right and left sides had a calculated t of -1.193 and the t-table value with df 14 at the 5% significance level was 2.14. p = 0.253, because p > 0.05 there is no significant difference. So it can be concluded that there is no significant difference between lay-up shots from the right side and the left side for boys' basketball extracurricular members aged 11-14 years